Listening to patients with cancer: using a literary-based research method to understand patient-focused care. Issue 10 (16th October 2014) - Begley, Amanda; Pritchard-Jones, Kathy; Biriotti, Maurice; Kydd, Anna; Burdsey, Tim; Townsley, Emma
Abstract : Objective: In spite of considerable attention, patients diagnosed with cancer continue to report poor experiences of care. The root causes of this remain unclear. This exploratory study aimed to investigate new ways of understanding the experience of patients with cancer, using a literary-based research approach. Design: Interviews were undertaken with four patients diagnosed with high-grade brain cancers at least 6 months from diagnosis and with people (n=5) identified by the patients as important in their care pathway. Interview transcripts were analysed by humanities academics as pieces of literature, where each patient's story was told from more than one person's perspective. The academics then came together in a facilitated workshop to agree major themes within the patient experiences. The themes were presented at a patient and carer event involving 70 participants to test the validity of the insights. Results: Insights into the key issues for patients with cancer could be grouped into six themes: accountability; identity; life context; time; language; rigour and emotion. Patients often held a different perspective to the traditionally held medical views of what constitutes good care. For example, patients did not see any conflict between a doctor having scientific rigour and portraying emotion. Conclusions: One key feature of the approach was its comparative nature: patients often held different views from those traditionally held by physicians of what constitutes health and good outcomes. This revealed aspects that may be considered by healthcare professionals when designing improvements. Proposals for further testing are discussed, with a particular emphasis on the need for sensitivity to individual differences in experiences.